Needs Analysis of Mandarin Language Learning Assisted by the Wordwall Game Application on Students a University in Padang - Ani Kariyati; Syahrul Ramadhan; Mukhaiyar Mukhaiyar; Ridha Hasnul Ulya (STAI Hubbulwathan Duri, 2024)
In the digital era, the integration of technology in education is becoming increasingly crucial to enhance student engagement and learning outcomes. One prominent tool in the context of Mandarin language instruction is Wordwall, a game-based learning platform that offers various interactive activities. This article aims to elucidate and evaluate the benefits of using Wordwall in the context of Mandarin language teaching and learning. The research conducted is of a descriptive nature. The respondents for this study were 52 students at Padang State University enrolled in Mandarin language courses. The subjects of this research consisted of 52 UNP study program students (45 women and 7 men) aged between 19 and 20 years who were selected using the random sampling technique.Data collection utilized a questionnaire through Google Forms and assessments of quizzes on the Wordwall game. The research data were analyzed qualitative by conducting validity tests, reliability tests, and classical assumption tests. The research findings conclude that learning with Wordwall makes the learning process easy, enjoyable, and assists students in understanding Mandarin. Furthermore, the implications of this research suggest that learning through the application of play techniques using the Wordwall game is highly suitable for beginner Mandarin language learners.